Health and welfare of rabbits farmed in different production systems. (9th January 2020) - ,; Saxmose Nielsen, Søren; Alvarez, Julio; Bicout, Dominique Joseph; Calistri, Paolo; Depner, Klaus; Drewe, Julian Ashley; Garin‐Bastuji, Bruno; Gonzales Rojas, Jose Luis; Gortázar Schmidt, Christian; Michel, Virginie; Miranda Chueca, Miguel Ángel; et al.
Abstract: The AGRI committee of the European Parliament requested EFSA to assess the welfare of rabbits farmed in different production systems, including organic production, and to update its 2005 scientific opinion about the health and welfare of rabbits kept for meat production. Considering reproducing does, kits and growing rabbits, this scientific opinion focusses on six different housing systems, namely conventional cages, structurally enriched cages, elevated pens, floor pens, outdoor/partially outdoor systems and organic systems. To compare the level of welfare in the different housing systems and rabbit categories, welfare impact scores for 20 welfare consequences identified from the literature were calculated, taking their occurrence, duration and severity into account. Based on the overall welfare impact score (sum of scores for the single welfare consequences), obtained via a 2‐step expert knowledge elicitation process, the welfare of reproducing does is likely (certainty 66–90%) to be lower in conventional cages compared to the five other housing systems. In addition, it is likely to extremely likely (certainty 66–99%) that the welfare of kits is lower in outdoor systems compared to the other systems and that the welfare is higher in elevated pens than in the other systems. Finally, it is likely to extremely likely (certainty 66–99%) that the welfare of growing rabbits is lower in conventional cages compared to the other systems and that the welfare is higher in elevated pens than in the other systems. Ranking of the welfare consequences allowed an analysis of the main welfare consequences within each system and rabbit category. It was concluded that for reproducing does, as well as growing rabbits, welfare consequences related to behavioural restrictions were more prominent in conventional cages, elevated pens and enriched cages, whereas those related to health problems were more important in floor pens, outdoor and organic systems. Housing in organic rabbit farming is diverse, which can result in different welfare consequences, but the overall welfare impact scores suggest that welfare in organic systems is generally good.